(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. This study aimed to investigate the effect of vitamin D on the pathologic changes of podocyte β-catenin and P-cadherin and podocyte permeability induced by diabetic conditions. Materials and Methods. We cultured mouse podocytes under normal glucose (5 mM, control); high glucose (HG, 30 mM); advanced glycosylation end products (AGE)-added; and HG plus AGE-added conditions and treated with vitamin D. The distribution of podocyte β-catenin and P-cadherin was shown by confocal microscopy, and protein levels of β-catenin and P-cadherin by Western blotting. Podocytes were incubated with vitamin D at the concentrations of 10 nM and 50 nM for 6, 24, and 48 hours. Results. The dextran filtration through monolayered podocytes tended to increase in AGE and HG condition compared to that in B5 at 16 hours in permeability assay, which was improved by vitamin D. In confocal imaging, the distribution of β-catenin and P-cadherin were internally concentrated by diabetic conditions, which was ameliorated by vitamin D. In Western blotting, HG and AGE decreased β-catenin protein levels at 6, 24, and 48 hours and vitamin D improved the decreased β-catenin protein levels at 6, 24, and 48 hours. Advanced glycosylation end products also decreased P-cadherin protein amount by 22.9% and 59.1% (P <.01) at 24 hours, respectively, which was improved by vitamin D. Conclusions. Our results suggest that HG and AGE have an influence on the redistribution of β-catenin and P-cadherin and amount of β-catenin protein of podocytes, thereby causing hyperpermeability, which can be reversed by vitamin D.